Inverting operations in operads - Basterra, M; Bobkova, I; Ponto, K; Tillmann, U; Yeakel, S (Elsevier, 2017)
We construct a localization for operads with respect to one-ary operations based on the Dwyer-Kan hammock localization [2]. For an operad O and a submonoid of one-ary operations W we associate an operad LO and a canonical map O → LO which takes elements in W to homotopy invertible operations. Furthermore, we give a functor from the category of O-algebras to the category of LO-algebras satisfying an appropriate universal property.